PENGARUH SUPPLY CHAIN MANAGEMENT TERHADAP OPERASIONAL PERUSAHAAN DAN KENDALA PROCUREMENT SISTEM ERP PADA PT UNILEVER INDONESIA TBK - Maharani, Delby; Haris, Haris; Aprillia, Novi; Kelly; Andryanto; Marthin, Ricko; Flowerensia, Dionna; Feby; Cuandra, Fendy; Zai, Immanuel (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research aims to determine the effect of Supply Chain Management and constraints of existing ERP systems in PT Unilever Indonesia Tbk is a company engaged in the household production industry by offering food products, beverages, kitchen needs, to toiletries. In an effort to develop its business operations, it is known that PT Unilever Indonesia Tbk implements its management strategy through ERP and Supply Chain Management systems. The ERP system at PT Unilever Indonesia Tbk functions as an information integration tool for all company stakeholders, while Supply Chain Management functions as a tool for monitoring the flow of goods to consumers and the amount of inventory. Thus, the two strategies are related to the certainty of the performance of Unilever employees. This paper aims to analyze the performance and the relationship between supply chain management, and the effect of the ERP system implemented by Unilever companies on operational performance through interaction and communication of information in order to be efficient in implementing supply chain management strategies and ERP systems. The research method uses a document study approach, as well as primary and secondary data collection techniques. The results of the study reveals that the Supply Chain Management strategy of PT Unilever Indonesia Tbk has four components, namely supply chain uncertainty, management of economies of scale, selection of transportation modes, and product inventory control; as well as the ERP and Supply Chain Management systems of PT Unilever Indonesia Tbk have a positive and significant impact on the company's performance so as to obtain profits and achieve company goals.